Factors influencing Financial Management in Public Secondary Schools in Nakuru County, Kenya - Munge, M. N.; Kimani, Elijah M.; Ngugi, D. G. (My University, 2016)
Proper management of finances in secondary schools is very imperative to their operations. There are, however, serious financial challenges in public secondary schools in Kenya as characterized by unprecedented high fees charged on students. This study evaluated the factors influencing financial management in public Secondary Schools in Nakuru County. Specifically, it analyzed the influence of budget management and financial controls on financial management. The study was guided by budget, financial control, and agency theories. The study adopted a cross-sectional survey research design. The study targeted heads and bursars of public secondary schools in Kenya. The accessible population constituted all the 172 school heads and 172 bursars of public secondary schools in Nakuru County. Stratified random sampling method was adopted to draw a sample of 78 from the accessible population. A structured questionnaire was used to collect data. A pilot study was conducted before the main study in order to examine the reliability and validity of the research questionnaire. The Cronbach alpha coefficient was used to text reliability while the university supervisor was consulted to determine the content validity of the research questionnaire. Data analysis was aided by the Statistical Package for Social Sciences analytical tool. Data analysis encompassed both descriptive and inferential statistics. Study findings were presented in form of tables. The study established that budget management and financial controls positively and significantly influenced financial management. The study recommended that public secondary schools should have effective budget management mechanisms and strong financial controls.
Keywords: Budget management; financial challenges; financial controls; financial management; public secondary schools